Peningkatan Kemampuan Pemahaman Matematis Dan Penalaran Matematis Melalui Problem Based Learning (PBL) Siswa Sekolah Menengah Pertama - ., Topik (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2020)
The research aims to study of improvement mathematical understanding and mathemacal reasoning. The design research is control group non-equivalen pretest and posttest. The population of all private secondary school in west bandung. The selection of a cluster sampling (area sampling) i.e. eighth class private secondary boarding school Darun Nasya. The instrument used are mathematical understanding, mathemacal reasoning and observation sheets. The analysis of quantitative datum using two way anova test. Research results : (1) there was no difference in improvement of the ability of mathematical understanding; (2) there is a deffernce in mathematical reasoning ability improvement; (3) there is a defference in mathematical reasoning ability improvement KAM among group with KAM hight group, the other group there is no defference; (4) there is no intreraction between the learning model and KAM to improvement ability mathematical understanding, mathemacal reasoning